Bibliometric Analysis Of Scientific Production In SCOPUS On The Relationships Between Humans And Nature With An Emphasis On Well-Being And Mental Health - Clavijo-Gallego , Tulio Andrés; Sánchez-Castillo , Verenice; Eslava-Zapata , Rolando (Journal of Ecohumanism, 2024)
There is a large and well-documented body of scientific literature that highlights the positive impact of nature on individuals' well-being and mental health. In this research, the authors propose a bibliometric analysis of the relationship between these variables and how they relate to mental health. To this end, the researchers selected studies in Spanish and English that were indexed in SCOPUS and published between 2018 and 2023. For the data analysis, the authors used VOSviewer and analyzed annual productivity networks, thematic trends, and keyword co-occurrence. As a result, we were able to identify three key trends in the literature, which revolved around the psychological benefits of exposure to natural environments, ecotherapy, and the sociocultural and environmental dimensions of these relationships. We conclude that current research prioritizes applied approaches, such as therapeutic interventions, but pays less attention to inequalities in access to natural environments. This study provides a systemic view of the field, useful for guiding future research toward gaps such as the role of urbanization and environmental justice.